Evaluation of Reference Interval of Serum Uric Acid Level During Pregnancy in Tertiary Care Hospital of Rawalpindi - Ain, Qurat Ul; Gilani, Mehwish; Asif, Naveed; Akram, Ammad; Uttra, Khurshid Muhammad; Siddiq, Amer (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the reference interval of uric acid in uncomplicated pregnancies. Study Design: Cross-sectional study. Place and Duration of Study: Pathology Department, Armed Forces Institute of Pathology, Rawalpindi Pakistan. Methodology: Data was collected from 807 pregnant females after informed consent. Healthy females of first and secondtrimester gestational amenorrhea with no previous significant surgical, medical and gynecological/obstetric history were included. In contrast, patients on drugs like anti-epileptics, anti-hypertensives, steroids, and poor obstetric history were excluded. Information regarding dietary, medical and family history and the use of tobacco, beverages, and current physical activity was collected using a standard questionnaire. Reference Interval was computed by using the 3rd and 97th percentile systems. Results: Mean age of study participants in the first trimester of pregnancy was 22.37 ± 2.54 years, while in the second trimester was 27.14 ± 3.62 years. Data was segregated into three age groups: 18-29 years (186, 23%), 30-35 years (452, 56%) and 36-43 years (169, 21%). Uric acid levels observed in the first and second trimesters were 95.8-260.14 umol/l and 96-268 umol/ respectively. Conclusion: Serum Uric Acid levels differed in normal pregnancy compared to the non-pregnant state. Moreover, this study also provides optimal reference intervals of uric acid levels for pregnancy’s first and second trimesters.